The effect of undergone bypass surgery on the percutaneous coronary intervention results / does previous coronary artery bypass surgery complicate the subsequent percutaneous coronary intervention? - Balin, Mehmet (My University, 2018)
Objective: Recurrent revascularization is frequently needed in despite to the modern treatment options of coronaryartery disease. Recurrent revascularization has need special caution in the setting of previous coronary artery bypasssurgery (CABG). There are very few studies to investigate possible adverse effects of prior CABG on percutaneouscoronary interventions (PCI). This study investigated that PCI results of the patients with prior CABG.Method: Patients who underwent PCI screened retrospectively. Consecutive 100 patients had been prior PCI (group 1),and 100 patients had been prior CABG (group 2) were enrolled to the study. The patients were not enrolled in the study;index PCI underwent bypass graft or total occluded lesion or instant lesion or in the setting of ST elevation myocardialinfarction or bifurcation stenting was done.Results: Group 1 and group 2 were similar in terms of age and gender. No statistically significant difference wasobserved between other demographic features. The lesion severity was not significantly different between the groups. Inthe CABG group, the intervention was more frequent to the circumflex artery lesion; while in the PCI group,intervention to the left anterior descending artery lesion was more frequent. Factors that made the procedure difficultwere similar in both groups. There was no significant difference between the two groups regarding lesions longer than20 mm and diffuse coronary artery disease. Balloon and stenting were more frequent in the CABG group, and directstenting was more frequent in the PCI group (p<0.05) Balloon dilatation was found to be more frequent in the CABGgroup. The duration of the procedure, number of angiographic frames and films, amount of contrast material used weresignificantly higher in the CABG group, as the difference between the two groups was not significant regarding balloonpressures applied during stenting. Previous CABG history was found to be an independent variable for the duration ofthe procedure and the number of angiographic frames. Prior CABG also has a significant correlation with prolongedintervention duration, radiopaque volume, and cine-angiography film and frame counts when controlling for intervenedartery and prior index intervention time interval.Conclusions: PCI was associated with prolonged intervention duration, higher radiopaque volume and higher radiationexposure when implanted in patients with prior CABG. The physician should be alert and precautionary for morecomplex PCI in patients with prior CABG.
Keywords: Genel ve Dahili Tıp